ADAPTATION AND VALIDATION TEST OF FEAR INTIMACY SCALE QUESTIONNAIRE FOR INDONESIAN UNIVERSITY STUDENT - Teguh Fachmi; Hasbi Wahyudi; Yahdinil Firda Nadhiroh; Wulan Fauzia (International Conference on Social and Islamic Studies, 2021)
The aims of this study is to test the reliability and validity of Fear of Intimacy scale thatmeasures individual anxiety and anxiety in having close relationships or intimacy inromantic relationships which introduced by Deschutner and Thelen (1991). Several itemshave developed from previous studies there are eight items taken and developed fromthe intimacy development inventory questionnaire and two items taken from the intimacysubscale of Erikson's subscale (Deschutner and Thelen, 1991). The scale adaptationprocess that the researcher did in this study refers to the journal Guidelines for theProcess of Cross-Cultural Adaptation of Self-Report Measures (Beaton, 2000).Distribution of data and samples of data was carried out through Google Formsapplication, where the researcher distributed questionnaire links through social media thatmet the research population criteria. The research population criteria set by theresearcher is for university students who have an age range of 18-24 years. The samplingtechnique used in this research is accidental sampling. Respondents in this study were235 students. To test the validity of the measurement scale, the researcher usedConfirmatory Factor Analysis (CFA) with Lisrel software. The results of the constructvalidity test on the Fear of Intimacy Scale, shows that the items on this scale aresignificantly unidimensional, means that, they only measure the construct of the fear ofintimacy dimension. In addition, the results of the translation process are also consideredgood, because there is no difference in meaning between the results of the backtranslation and the initial scale. Respondents can easily understand the statementscontained in this scale. Based on the results of the CFA analysis with the Lisrel program,the fear of intimacy scale consist of 32 question, however it is known that there are twoitems that have a t value below 1.96, so that the significant items on this scale are 32items consisting of 3 dimensions.